Functional (psychogenic) symptoms in Parkinson's disease. Issue 12 (4th June 2013) - Pareés, Isabel; Saifee, Tabish A.; Kojovic, Maja; Kassavetis, Panagiotis; Rubio‐Agusti, Ignacio; Sadnicka, Anna; Bhatia, Kailash P.; Edwards, Mark J.
ABSTRACT It has been reported that patients who have Parkinson's disease have a high prevalence of somatisation (functional neurological symptoms) compared with patients who have other neurodegenerative conditions. Numerous explanations have been advanced for this phenomenon. Here, with illustrative cases, we discuss this topic, including its clinical importance, and suggest a link between the pathophysiology of Parkinson's disease and the proposed propensity to develop functional symptoms. © 2013 International Parkinson and Movement Disorder Society